Pemerolehan Bahasa Anak Usia 3 Tahun Pada Video Youtube - Azizah Nadiani; Hendra Setiawan (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research aims to determine the language acquisition of children aged 3 years which includes the level of syntax by using the theory of Mean Length Utterance (MLU) which was initiated by Brown. This type of research is descriptive qualitative research with using two data collection techniques, listen and record. The data that has been obtained is described, and then concluded. Data taken by researchers from a 3-year-old child with the initials SAA on a youtube video. The results of this research the 3-year-old child has a very high value for speech at his age, namely with a value of 3.0 which in Brown's theory is at level VII. Children with the initials SAA are able to speak using standard language well in their daily lives. However, in some of his utterances, this 3-year-old child has not been able to pronounce the phoneme /r/ clearly, the child releases the phoneme /r/ then disappears into /l/. This happens because of several factors such as family factors and environmental factors.